Assessing the mask-wearing habit as a contributing factor for COVID-19–associated mucormycosis - Bhawna Saini; Ambika Gupta; Suman Bisla; Komal Kumia; Shubhangi Shukla; Kime Yama (Journal of Family Medicine and Primary Care)
Introduction: Association of mask-wearing habit and mucormycosis. Context: During the second wave of the COVID-19 pandemic, there was an absurd surge in cases of mucormycosis. COVID-19–associated mucormycosis (CAM) was found to be associated with the presence of diabetes, use of systemic steroids, prolonged use of masks, and others. The improper use of masks was proposed to be treacherous. Methods and Material: A case–control study was planned in which the patients coming to the dental OPD over a period of 6 months were asked to fill out a questionnaire validated by experts. Results: A total of 100 participants were included in the study. Out of 100 patients, 43 opted for surgical/N95 masks, whereas others were seen using different fabric mass. Mask-wearing habits are not a contributing factor for CAM. (P value > 0.005). Conclusions: Such studies give us an idea of the impact of hygiene habits on infectious diseases, further studies are required on a larger sample.